The impact of socioeconomic factors on quality of life and functional impairment in patients treated for oropharyngeal carcinoma - Milovanović, Jovica; Andrejić, Dragoslava; Jotić, Ana; Djukić, Vojko; Tošković, Oliver; Savić-Vujović, Katarina; Pavlović, Bojan; Stojković, Goran; Banko, Bojan; Milovanović, Andjela; Artiko, Vera (Vojnosanitetski pregled, 2021)
Backround/Aim. Considering the distinct increase in the incidence of oropharyngeal cancer over oral cavity cancers and changing epidemiology with human papilloma virus (HPV) infection emerging as an important risk factor, there is a need to establish better treatment choices in specific groups of patients with oropharyngeal cancer. The aim of this study was to assess the quality of life (QOL) and functional performance and the impact of different demographical data, stage of disease, and treatment type on these parameters in patients with oropharyngeal cancer with successfully achieved locoregional control a year after the treatment. Methods. Study included 87 patients who underwent QOL and functional impairment assessment 12 to 14 months after finished oncological treatment with the following questionnaires: the European Organization for Research and Treatment of Cancer Quality-of Life-Questionnaire-C30 (EORTC QLQ-C30), European Organization for Research and Treatment of Cancer Quality of- Life Questionnaire-Head and Neck 35 (EORTC QLQ-H&N35) and The Karnofsky Performance Scale (KPS). Results. Specific groups of patients had significantly different post-treatment QOL scores. The factors associated with the worse QOL scores were female gender, not being in a partnership, level of education and HPV status. Conclusion. Clinicians should consider socioeconomic factors and HPV status in planning the recovery after treatment of patients with oropharyngeal carcinoma. Gender, education level and employment are the variables that form a certain risk profiles associated with the lower QOL.